Accountancy and financial management (SYBCom) - Chopde L.N., Choudhari D.H., Mehta K., Gandhi M.A. and others (Sheth Pub., Mumbai, 2005)
Commerce
ENGLISH
Keywords: Accountancy and financial management (SYBCom); Commerce; Commerce